ANALISIS USAHA BUDIDAYA IKAN LELE DUMBO (Clarias gariephinus) DI DESA WONOSARI KECAMATAN BONANG KABUPATEN DEMAK (Studi Kasus Desa Wonosari Kecamatan Bonang Kabupaten Demak) - Ali Rochman; Dewi Hastuti; endah subekti (Universitas Wahid Hasyim, 2014)
The purpose of this study was to determine the activities of Clarias gariephinus fish farming, profitability and feasibility of Dumbo catfish aquaculture activities, and opportunities for the development of fish farming in the Wonosari Village Bonang District Demak Regency. The method used is a case study, the sampling method of purposive sampling as many as 20 people. Data analysis using financial analysis includes analysis of BEP and the RC ratio. The results of this study are the activities of Clarias gariephinus fish farming is done individually by technical enlargement Clarias gariephinus per 10,000 individuals per 100 m2 of required capital = Rp. 7,875,000.- harvest per cycle,the rate of profit and feasibility of aquaculture fish Clarias gariephinus per 10,000 individuals per 100 m2, with the total cost (TC) of Rp. 7,875,000.-. total receipts (TR) of the amount of the production 750 kg per cycle of harvest by = Rp. 13,000.- per kg. The selling price is Rp. 9,750,000.-, The average income of Rp. 1,875,000.-, RC ratio Value of 1.23, and BEP(Q) of 605.76 kg, BEP (IDR) of Rp. 10,500.- per harvest cycle per 100m2 per10,000 head, the chances of developing Clarias gariephinus fish farming in the Wonosari Village Bonang District Demak Regency, can be done with the intensification and extension and developments nature by cooperating with kooparatif invenstor/banking as well as the development of managerial by establishing cooperative. The conclusion of hypothesis in accepted in view of the value RC ratio of 1.23, and BEP(Q) of 605.76 kg, BEP (IDR) of Rp. 10,500.- per harvest cycle per 100 m2 per 10,000 head, so that the cultivation of Clarias gariephinus fish deserves to be cultivated. Keywords: Benefits, costs, Catfish farming, feasibility, income.